Code design with high rates based on quasi-orthogonal space-time block code - WANG An-guo; SHEN Qiong; NIE Zhong-er (Tongxin xuebao)
In order to meet the needs of high-speed and large-capacity in communication system,the novel non-orthogonal space-time block code with code rates 2 and 1.5 were proposed,respectively.The simplified conditional maximum-likelihood algorithm is adopted to reduce the decoding complexity.The simulation results show that the channel capacities of proposed code are very close to the actual value,and the BER performance is better than that of the orthogonal and quasi-orthogonal codes.